The Effectiveness of an Experiential Learning (ExL) on the Students’ Reading Comprehension - Maria Ulfa; J. Priyanto Widodo; Shierly Novalita Yappi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The purpose of this study was to determine the effectiveness of 'Experiential Learning’ (ExL) on the students’ reading comprehension at MA Nurul Islam Pungging, Mojokerto, East Java, Indonesia. The pre-experimental design was used in this study. The research samples consisted of 32 students from Class XI-IPA 2, with one representative from experimental group, chosen using a purposive sampling technique. The data were analyzed using the t-test and the analysis test was performed using the ITEMAN software. The results showed the Sig. value of (Sig. (2-tailed)) was .003, which was less than the level of significance of .05. It was determined that the null hypothesis (Ho) was ‘rejected’, and that the alternative hypothesis (Ha) was ‘accepted’. Then, it was discovered that, on average, the post-test group had a mean of 88.4, which was significantly higher than the mean of the pre-test group, which was 75.6. It has been determined that Experiential Learning (ExL) is effective in improving the students’ reading comprehension. Students’ academic performance may be improved if teachers are encouraged to use ExL to teach the concept of teaching approach. So, other researchers are suggested to investigate similar research by applying ExL in other methods and other English skills.